Computed tomography derived predictors of permanent pacemaker implantation after transcatheter aortic valve implantation: a meta-analysis. (25th November 2020) - Maier, O; Zeus, T; Jung, C; Westenfeld, R; Polzin, A; Kelm, M; Veulemans, V
Abstract: Background: Transcatheter aortic valve implantation (TAVI) is a well-established alternative to surgery for the treatment of patients with severe symptomatic aortic stenosis at high and intermediate surgical risk. Unfortunately, the occurrence of electrical conduction disturbances remains one of the most frequent complications of the procedure. While the impact of electrocardiographic and procedural predictors on PPI is well examined, there is still a lack of knowledge regarding anatomical predictors screened by multislice computed tomography (MSCT). Purpose: We performed a meta-analysis to summarize available studies that reported the incidence of PPI after TAVI with new-generation devices and provided raw data for preprocedural MSCT. Methods: The authors conducted a literature search in PubMed database until December 31, 2019 to identify studies that investigated preprocedural MSCT data and rate of PPI following TAVI with new-generation devices. Twelve observational studies (n=3133) met inclusion criteria for final analysis. Results: PPI was performed in 509 patients (16.2%) after TAVI, mostly due to high degree atrioventricular (AV) block (80.8%). The rate of PPI varied widely from 7.9% to 35.8% in individual studies. Regarding secondary endpoints' analysis of relative risk (RR) and mean difference (MD) electrocardiographic PPI-predictors after TAVI appeared to be pre-existing atrial fibrillation (AF) (RR 1.21; 95% CI 1.05–1.40; p=0.008), right bundle branch block (RBBB) (RR 4.22; 95% CI 3.30–5.41; p<0.0001) and AV block grade I (RR 1.63; 95% CI 1.16–2.29; p=0.005). Patients requiring PPI had larger annulus perimeter (MD 1.66 mm; 95% CI 0.67–2.66 mm; p=0.001) and shorter membranous septum length (MD −0.86 mm; 95% CI −1.74–0.02 mm; p=0.05) assessed by preprocedural MSCT. Concerning calcium load of device landing zone, pacemaker dependent patients showed increased calcification of the non-coronary cusp (MD 39.76 mm 3 ; 95% CI 18.60–60.93 mm 3 ; p=0.0002), the left-coronary cusp (LCC) (MD 47.60 mm 3 ; 95% CI 19.40–75.81 mm 3 ; p=0.0009) and the total left ventricular outflow tract (LVOT) (MD 19.17 mm 3 ; 95% CI 6.68–31.66 mm 3 ; p=0.003). Lower implantation depth (MD 0.83 mm from NCC; 95% CI 0.20–1.47 mm; p=0.01) and oversizing by annulus diameter/area (MD 1.76%; 95% CI 0.68–2.84%; p=0.001) were procedural predictors of PPI following TAVI. Conclusion: This structured meta-analysis proved PPI rate in 16.2% of patients following TAVI. Beside well-known electrocardiographic (AF, RBBB, AV block grade I) and procedural predictors (implantation depth, oversizing) this meta-analysis showed for the first time that MSCT derived anatomical values (annulus perimeter, membranous septum length) and distribution of device landing zone's calcification (NCC, LCC, LVOT) are associated with increased risk of PPI following TAVI. Funding Acknowledgement: Type of funding source: None